Second Harmonic Generation Confocal Microscopy of Collagen Type I from Rat Tendon Cryosections - Theodossiou, Theodossis A. (Biophysical Society, 2006)
We performed second harmonic generation (SHG) imaging of collagen in rat-tendon cryosections, using femtosecond laser scanning confocal microscopy, both in backscattering and transmission geometries. SHG transmission images of collagen fibers were spatially resolved due to a coherent, directional SHG component. This effect was enhanced with the use of an index-matching fluid (n(i) = 1.52). The average SHG intensity oscillated with wavelength in the backscattered geometry (isotropic SHG component), whereas the spectral profile was consistent with quasi-phase-matching conditions in transmission geometry (forward propagating, coherent SHG component) around 440 nm (λ(p) = 880 nm). Collagen type I from bovine Achilles tendon was imaged for SHG in the backscattered geometry and its first-order effective nonlinear coefficient was determined ([Formula: see text]) by comparison to samples of inorganic materials with known effective nonlinear coefficients (LiNbO3 and LiIO3). The SHG spectral response of collagen type I from bovine Achilles tendon matched that of the rat-tendon cryosections in backscattered geometry. Collagen types I, II, and VI powders (nonfibrous) did not show any detectable SHG, indicating a lack of noncentrosymmetric crystalline structure at the molecular level. The various stages of collagen thermal denaturation were investigated in rat-tendon cryosections using SHG and bright-field imaging. Thermal denaturation resulted in the gradual destruction of the SHG signal.